Constraints on supermassive black hole spins from observations of active galaxy jets. Issue 9 (November 2013) - Kun, E.; Wiita, P.J.; Gergely, L.Á.; Keresztes, Z.; Gopal‐Krishna; Biermann, P.L.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract We discuss the origin of the low‐energy cutoff, or LEC, seen in the radio spectra of many extragalactic jets and relate this to the spin of the supermassive black holes that presumably power them. Pion decay via proton‐proton collisions is a possible mechanism to supply a secondary positron population with a low energy limit. We expect that pion production would occur in advection dominated accretion flows or ADAFs. In radiatively inefficient ADAFs the heat energy of the accreting gas is unable to radiate in less than the accretion time and the particle temperature could be high enough so that thermal protons can yield such pion production. Strong starbursts are another option for the injection of a truncated particle population into the jet. The role of both mechanisms is discussed with respect to the black hole spin estimate. The energy demanded to produce the pion decay process involves a minimum threshold for kinetic energy of the interacting protons. Therefore the mean proton speed in the flow can determine whether a LEC is generated. In ADAFs the random velocity of the protons can exceed the minimum speed limit of pion production around the jet launching region in the innermost part of the flow. Finally we summarize the additional work needed to put the model assumptions on a more rigorous basis. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)